2014
DOI: 10.1097/iop.0000000000000003
|View full text |Cite
|
Sign up to set email alerts
|

Severe Neutropenia Presenting With Candida Albicans Eyelid Abscess in a 1-Year-Old Child

Abstract: A previously healthy 1-year-old boy presented with a right lower eyelid abscess. Oral and topical antibiotics were initiated, and the lesion was drained and explored. Despite medical and surgical treatment, the abscess failed to resolve completely and formed again 1 month later. A second incision and drainage procedure was performed, and Candida albicans grew in cultures. Additional workup revealed severe neutropenia with an absolute neutrophil count of 0.18 k/μl (1.19-7.21 k/μl). The abscess resolved after 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Costin et al [ 4 ] reported recurrent C. albicans eyelid abscess in a 1-year-old child with severe neutropenia. Chen et al [ 5 ] described facial C. albicans cellulitis that occurred 2 months after steroid injection treatment in a patient with oral submucous fibrosis and unknown diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Costin et al [ 4 ] reported recurrent C. albicans eyelid abscess in a 1-year-old child with severe neutropenia. Chen et al [ 5 ] described facial C. albicans cellulitis that occurred 2 months after steroid injection treatment in a patient with oral submucous fibrosis and unknown diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…Facial abscess caused by C. albicans infection is a rare condition even in immunocompromised patients and only a few cases have been reported [ 4 7 ]. Candidal infection of subcutaneous tissue may result from direct contact, inoculation injury or hematogenous spread [ 8 ].The authors report a case of multiple facial candidal abscesses caused by self-administered acupuncture in an undiagnosed diabetes mellitus patient.…”
Section: Introductionmentioning
confidence: 99%
“…1 This was a 28-day-old girl, born through a cesarean delivery, after an uneventful gestation of 38 weeks; her birth weight was 2,030 g. The parents of the infant were 26 years old, nonconsanguineous, and had no family history of similar disease; the mother was a primigravida. This patient had syndromic features similar to those of our previous patient: triangular face, macrocephaly, prominent scalp veins, mandibular hypoplasia, sparse A 28-day-old girl with neonatal progeroid syndrome and bilateral congenital upper eyelid entropion.…”
Section: Another Case Of Neonatal Progeroid Syndrome and Bilateral Comentioning
confidence: 98%